Valorization of Shrimp Shell Waste: Comparative Phytochemical Composition and Bioactivity of Parapenaeus longirostris and Aristeus antennatus - Essaid Zeghdoudi; Ahmed Nouar; Mohammed Cheurfa; Chaimaa Noun; Imane Kouider Mohammadi; Wahyu Aristyaning Putri; Valentina Fernandes Domingues (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
The valorization of marine by-products represents a promising approach for discovering novel bioactive compounds. This study presents a comparative phytochemical and bioactivity assessment of shrimp shell waste extracts from Parapenaeus longirostris and Aristeus antennatus species, which are prevalent on Algerian coasts. The objective of this study is to evaluate their potential as a source of biologically active compounds, with a particular focus on those compounds that possess anti-inflammatory and antidiabetic properties. The methodology entailed the extraction of chemical compounds. The subsequent procedure involved the utilization of shrimp residues, which were then subjected to a comprehensive compositional analysis. This analysis was then followed by an evaluation of their biological activity. The results obtained demonstrated the presence of biologically effective compounds, with the extracts exhibiting notable anti-inflammatory and antidiabetic activity. White shrimp (P. longirostris) was found to be particularly efficacious in both activities, showing particular promise in diabetes-related inhibition. This finding indicates the potential of valorization. It is evident that these marine by-products have the potential to serve as a promising natural resource for the development of value-added products. It is evident that these initiatives facilitate novel advancements in the domains of health and industry, thus underpinning the blue economy within the paradigm of sustainable development.